Women Entrepreneurs' Performance : Microfinance Factors With Mediating Effect of Opportunity and Moderating Effect of Attitude - Ekpe, Isidore (2011)
The purpose of this study was to investigate the relation- ship between micro-finance related factors (credit, savings, training and social capital) offered by micro-finance institutions and women entrepreneurs’ business performance with mediating influence of opportunity for entrepreneurial activity and the moderating influence of attitude towards micro-finance. However, the hypotheses were restated to reflect the component factors that resulted from the Exploratory Factor Analysis. For example, loan access represented credit, skill acquisition represented traininig , bonding represented social capital, opportunity for business improvement represented opportunity for entrepreneurial activity, ability to expand business and self-confidence in doing business represented attitude towards micro-finance, and women entrepreneurs’ sales performance represented women entrepreneurs’ business performance. A total of 280 women entrepreneurs participated in the survey through mail questionnaire; out of which 172 questionnaires were usable. However, after data cleaning, only data for 161 respondents were finally used for the data analysis. Descriptive statistics, multiple, linear and hierarchical regression analyses were used for data analysis and hypotheses testing. The study found that there were significant positive relationships between: loan access, skill acquisition and bonding; and women entrepreneurs’ sales performance which met Research Objective 1; skill acquisition and women entrepreneurs’ sales performance which met Research Objective 2; loan access and opportunity for business improvement of women entrepreneurs, skill acquisition and opportunity for business improvement of women entrepreneurs which met Research Objective 3; opportunity for business improvement and women entrepreneurs’ sales performance which met Research Objective 4; opportunity for business improvement of women entrepreneurs partially mediated the relationship between loan access, skill acquisition and bonding; and women entrepreneurs’ sales performance since only skill acquisition was significant which met Research Objective 5; ability to expand business partially moderated the relation- ship between loan access, skill acquisition, bonding and opportunity; and women entrepreneurs’ sales performance which met Research Objective 6. The study concludes that micro-finance factors are positively related to women entrepreneurs’ business performance as the models were, collectively, significant.